2012
DOI: 10.1002/jid.1715
|View full text |Cite
|
Sign up to set email alerts
|

Disability measures as an indicator of poverty: A case study from Viet Nam

Abstract: This paper examines the relationship between disability and poverty at a healthdemographic surveillance site in Viet Nam using alternative measures of disability severity. Analysis of the site population (n ¼ 65 400) is combined with interviews of 27 households containing members with disabilities. Results show that disability severity is positively associated with poverty. Results support recent efforts of the Vietnamese government to extend programmes of social protection for households containing members wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…In two communes in Vietnam, support from relatives, friends or the community for households with PWDs was not common; gifts and money were frequent on the occasion of New Year, but were not significant in value (Palmer et al, 2010). Another study reported that the Vietnamese government policy of "socialisation" which encourages communities to contribute money, food, clothing or moral support to PWDs and other disadvantaged groups was failing (Le et al, 2008).…”
Section: A Review Of the Evidencementioning
confidence: 95%
See 2 more Smart Citations
“…In two communes in Vietnam, support from relatives, friends or the community for households with PWDs was not common; gifts and money were frequent on the occasion of New Year, but were not significant in value (Palmer et al, 2010). Another study reported that the Vietnamese government policy of "socialisation" which encourages communities to contribute money, food, clothing or moral support to PWDs and other disadvantaged groups was failing (Le et al, 2008).…”
Section: A Review Of the Evidencementioning
confidence: 95%
“…Part of the reason for this is that cash benefits are generally low and set below the minimum wage to discourage disincentive effects (Gooding & Marriot, 2009). In Vietnam, cash transfers were described as being of "encouragement" value only (Palmer et al, 2010). In South Africa, however, the amount of the benefit is substantial, equal to about twice the per capita income for Africans (Mitra, 2010).…”
Section: A Review Of the Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…Disability, in particular, is a barrier often accompanied by economic and social hardships (Dalal, 2010;Choe, 2013;Palmer, 2012). Young adults with disabilities continue to have lower rates of employment than non-disabled peers (Gold, Fabian and Lucking, 2013).…”
Section: Psychological Self-sufficiencymentioning
confidence: 99%
“…Furthermore, Palmer et al (2012) and World Bank (2009) find that households with disabled persons own less assets compared to other households, while Trani and Loeb (2012) suggest that there is no such a relationship. Poverty when measured by household expenditure suggests that probability of being poor is higher with disability (Mont & Viet Cuong, 2011;Filmer 2008;Hoogeveen, 2005).…”
Section: Poverty: a Cause Or An Effect Of Disability?mentioning
confidence: 99%